The systematic development of an innovative DVD to raise awareness of preconception care. Issue 1 (27th February 2013) - Spence, Michelle; Harper, Roy; McCance, David R; Alderdice, Fiona A; McKinley, Michelle C; Hughes, Clare; Holmes, Valerie A
Abstract The purpose of this article is to describe the design, development and process evaluation of a preconception counselling resource (a DVD) for women with pre‐gestational diabetes. DVD design and development centred on two key stakeholders ('DVD user group' and 'professional advisory group') working alongside a professional multimedia company. The DVD user group provided feedback on preferred DVD style, and informed modifications and improvements. The professional advisory group prepared the script, and ensured content and face validity. Evaluation of the DVD's acceptability and usefulness was assessed among women with diabetes via a postal questionnaire. Development phase: the resulting DVD is a 45‐minute programme with three parts, featuring eight women with diabetes sharing their views and experiences, alongside an evidence‐based commentary. The programme focuses on the importance of preventing an unplanned pregnancy (highlighting contraception) and on essential planning advice. Evaluation phase: 97 women (89 with type 1 and 8 with type 2 diabetes) evaluated the DVD using a rating scale of 0–10. Mean (SD) scores were: 9.1 (1.3) for quality; 9.0 (1.4) for content; 8.8 (1.5) for interest; 8.7 (1.8) for usefulness; 7.8 (2.2) for knowledge acquisition; and 8.0 (2.1) for knowledge confirmation. This combined user and multi‐professional advisory group approach has produced an innovative and highly acceptable preconception counselling resource for women with diabetes. The development process and outcome evaluation are an important point of reference for future educational programmes. Future research will evaluate the impact of this preconception counselling resource on pregnancy planning indicators and pregnancy outcome. Copyright © 2013 FEND. Published by John Wiley & Sons, Ltd.